The Exceptional Ninth-Century BCE Northwestern Quarter at Tel Reḥov - Panitz-Cohen, Nava; Mazar, ʿAmiḥai 1942- (2022)
An exceptional architectural complex at Tel Reḥov dating to the last phase of the Iron IIA occupation in the ninth century BCE (Stratum IV) was uncovered in Area C, located on the northwestern and highest part of the lower mound. Each of the buildings belonging to this quarter, built exclusively of mud brick, had an exceptional architectural layout, while at the same time, they were interrelated and organized according to a preplanned agenda. All the buildings were completely destroyed by the severe fire that resulted in the abandonment of the lower city at the end of Stratum IV. The abundance of rich remains found in the destruction debris just below topsoil, many of them of a unique nature and reflecting quotidian, cultic, and industrial activities, as well as three inscriptions with personal names, indicate the special role played by this complex, particularly the largest and most exceptional: Building CP.